Mapping Miguel Covarrubias across Cultures and Disciplines - Racine, Nathaniel R. (Review of International American Studies, 2020)
In this paper, I explore the Pageant of the Pacific, a sequence of mural-maps painted by the Mexican artist and illustrator, Miguel Covarrubias, for the San Francisco International Exposition of 1939–1940. By placing these mural-maps within the larger context of cultural geography and Covarrubias’s own theories of comparative anthropology, they offer an artistic and poetic explanation of the relationships found among the cultures of the Pacific Rim, drawing connections across historical epoch and geographical region. Within Covarrubias’s own historical context, these maps provide an important visual link that crosses disciplinary boundaries, providing insight into the intellectual conversation of his era and, perhaps, providing a model for interdisciplinarity in the present age as well.